The Influence of Income and Consumption Patterns on the Welfare of MSMEs in Sidomulyo Village, Jember: Pengaruh Pendapatan Dan Pola Konsumsi Terhadap Kesejahteraan Umkm Di Desa Sidomulyo Jember - Izzah Dienillah; Putri Mega Utami Aulia; Supriyanto (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy. MSMEs contribute significantly to the Gross Domestic Product (GDP) and employment absorption. However, many MSMEs in rural areas have yet to achieve an adequate level of welfare. One of the factors influencing MSME welfare is income and consumption patterns. This study aims to examine the effect of income on the welfare of MSMEs, as well as the effect of consumption patterns on MSME welfare. This is a descriptive study using a quantitative approach. The sample was obtained through a survey of 139 respondents from a total population of 230 MSME actors, using a random sampling technique. Hypothesis testing was conducted using multiple linear regression analysis. The results show that income has a significant effect on the welfare of MSMEs, and consumption patterns also significantly affect MSME welfare. These findings contribute to MSME development, particularly in shaping empowerment policies that focus on enhancing economic capacity and promoting productive consumption behavior.